Inside Back Cover: Volume 2 Issue 2. (29th June 2021) - Yang, Niuwa; Chen, Dong; Cui, Penglei; Lu, Tingyu; Liu, Hui; Hu, Chaoquan; Xu, Lin; Yang, Jun
Abstract : Inside back cover image : Heterogeneous nanocomposites constructed by chemically distinct constituents are promising in electrocatalysis due to strong electronic coupling among their different domains. The exploration of noble metal‐containing heterogeneous nanocomposites in electrocatalysis has been blooming in the past and is still a hot topic in current scientific community. In principle, the optimization on both the composition and morphology of the domains for a composite catalyst is an effective way to boost its performance for a given electrochemical reaction. The authors herein demonstrate asynthetic strategy that combines the co‐reduction of Pt and Co precursors with a subsequent phosphating process for constructing heterogeneous nanocomposites consisting of Pt3 Co alloy nanoparticles and CoP2 nanorods, which exhibit good activity for methanol electrooxidation both in acidic and alkaline media. In comparison with their abundant studies in photocatalysis, the applications of noble metalcontaining nanocomposites for catalyzing electrochemical reactions are relatively limited. The authors therefore offer a vivid example to show the potential of heterogeneous nanocomposites in electrocatalysis and provide a competent way to produce electrocatalysts with cost‐effectiveness and desired efficiency. The challenges in this field, which are expected to further continue in the coming years, are to enlarge the selection of noble metals and semiconductors via innovative strategies for developing nanocomposites with more combinations, architectures, and higher complexity so that the coupling effect among their different domains could be maximized and optimized. This would render the heterogeneous nanocomposites more favorable for given technological applications. (DOI: https://doi.org/10.1002/smm2.1032 )